Evidence-Based Medicine, Systematic Reviews, and Guidelines in Interventional Pain Management: Part 3: Systematic Reviews and Meta-Analyses of Randomized Trials - Manchikanti, Laxmaiah (Pain physician, 2009)
In recent years, progress and innovations in healthcare are measured by evidencebased medicine (EBM), systematic reviews, and meta-analyses. A systematic review is defined as, “the application of scientific strategies that limit bias by the systematic assembly, critical appraisal, and synthesis of all relevant studies on a specific topic.” In contrast, meta-analysis is the statistical pooling of data across studies to generate pooled estimates of effects. Meta-analysis usually is the final step in a systematic review. Systematic reviews and meta-analyses are labor intensive, requiring expertise in both the subject matter and review methodology, and also must follow the rules of EBM which suggest that a formal set of rules must complement medical training and common sense for clinicians to interpret the results of clinical research effectively. While expertise in the subject matter is crucial, expertise in review methods is also particularly important. Despite an explosion of systematic reviews and meta-analyses, the empiric research on the quality of systematic reviews has shown that not all systematic reviews are truly systematic, having highly variable quality, deficiencies in methodologic assessment of the quality of the included manuscripts, and bias. Even then, systematic review of the literature is currently the best, least biased, and most rational way to organize, cull, evaluate, and integrate the research evidence from among the expanding medical and healthcare literature. However, a dangerous discrepancy between the experts and the evidence continues to persist in part because multiple instruments are available to assess the quality of systematic reviews or meta-analyses. Steps in conducting systematic reviews include planning, conducting, reporting, and disseminating the results. The Quality of Reporting of Meta-analysis (QUOROM) statement provides a checklist and a flow diagram. The checklist describes the preferred way to present the abstract, introduction, methods, results, and discussion sections of the report of an analysis. This review describes various aspects of systematic reviews and meta-analyses of randomized trials with a special focus on interventional pain management. Key words: Randomized trials, pragmatic trials, evidence-based medicine, systematic reviews, meta-analyses, guidelines, bias, interventional pain management, Quality of Reporting of Meta-analysis (QUOROM), Cochrane reviews